KETIKA UMAT MENINGGALAKAN ULAMA: Perilaku Politik Umat Islam Pasca PRRI 1959-1972 - Mhd Ilham (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This research is historical research. Aims to reveal the shift in political preferences of the Ummah in Pasaman District after the PRRI rebellion. In this study it was found that ulama are the most significant historically-factual-implicative social elite. This can be seen from the existence and influence of the Muhammadiyah and the Masyumi party in the early 1950s to 1957, two organizations which were significantly influenced by the ulamas. After the PRRI rebellion in 1957 and the operation of mass destruction of the remaining PRRI sympathizers in this area in 1958, there was a shift in the socio-political preferences of the Muslims in Pasaman Regency. Shifts in a very fast time span. Ulama which has been considered as the main reference in determining political choices, shifts to other social elites, local non-clerical political elites. The PRRI rebellion left psychological trauma for Muslims in Pasaman District, which contributed greatly to changing the socio-political preferences of the Muslim Ummah and decreasing the level of Islamic belief in the ulamas.